PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBANTUAN KOMIK POP UP DENGAN MODEL PROBLEM BASED INSTRUCTION (PBI) SUB POKOK BAHASAN KUBUS DAN BALOK UNTUK SISWA SMP KELAS VIII - Zeila, Wida Zannah; Hobri, H; Suharto, S (Kadikma, 2014)
Abstract.The research aims to know process and result of developing of mathematics learning intruments based on Problem Based Instruction and assisted pop up comic for cube and cuboid topic at eighth grade of junior high school. The research development modle refers to 4D Thiagarajan models. The subject of research is students of VIIIG class SMPN 4 Jember in even semester academic year 2012-2013. The data of research are obtained by validation sheet, observation sheet of teacher and students activities, questionnaire, and evaluation test.The product of this research are lesson plan, student handbook, worksheet, evaluation test, and pop up comic.The validity of those product consecutively are 0,77; 0,81; 0,83; 0,81; 0,80. The average percentage of teacher activity is 90%, student activity is 90,7%, and student respond regarding learning tools is 81,8%.The result shows that the learning instruments qualifies validity, practical, and effective criteria. Key Words: Problem Based Instruction Model, pop up comic, cube and cuboid